Digital Archiving and the Preservation of Rickshaw Painting as Intangible Cultural Heritage in Bangladesh - Khan Mahadi Billah Lime Lime; Hamidul Huda Stevan Stevan (ELITE: Journal of English Language and Literature, 2025)
Rickshaw painting in Bangladesh is a distinct type of folk art that turns cycle rickshaws into colorful mobile canvases. The paintings represent themes from rural life, cinema, religion and national history, but are also a symbol of cultural identity and intangible heritage. In the past few decades this tradition has undergone serious decline due to modernization. This situation presents a research gap in the potential contribution of digital archiving towards the preservation & revitalization of rickshaw painting. The purpose of this research is to study the possibility of digital archives as a safeguarding tool for the artistic, cultural and social dimensions of this endangered tradition. The research is qualitative, relying on archival research, field observation of workshops, and oral history interviews with rickshaw painters and rickshaw pullers. It also examines how tools such as high-resolution photography, video documentation, oral history recordings, and virtual exhibitions can capture not only the artworks but also the techniques, stories, and apprenticeship systems behind them. Findings have suggested that digital archives can not only preserve the visual motif, but also the oral tradition, and can establish global access to the art, as well as new markets for artisans. However, challenges exist, especially in terms of authenticity, over commercialization and the rights of artists. The paper concludes by stating that community-centered and ethically designed digital archives can offer a sustainable model for rickshaw painting's living heritage preservation while amplifying its cultural value at the local and global levels.